Political parties - Tarakson, Stella (Sydney : Pearson Australia, 2011)
This series examines Australia's three levels of government: local, state and territory, and federal, as well as the political parties that have played an important role in Australia's political system. Each book includes a wealth of primary source material, contemporary and historical photographs, tables, maps and timelines. Ages 7-12.
Includes bibliographical references (p. 31) and index.
For primary school age.
Keywords: Political parties -- Australia -- Juvenile literature; Australia -- Politics and government -- Juvenile literature